SODIUM LAURETH SULFATE (SLS) DECORATED α-PbO NANOCRYSTALS: OPTICAL, STRUCTURE, AND MORPHOLOGY, PROPERTIES - Tikarahayu Putri; Iwan Syahjoko Saputra; Anjar Hermadi Saputro; Yogi Nopiandi Permana; Yoki Yulizar; Sudirman Sudirman (Jurnal Sains Materi Indonesia, 2021)
SODIUM LAURETH SULFATE (SLS) DECORATED α-PbO NANOCRYSTALS: OPTICAL, STRUCTURE, AND MORPHOLOGY PROPERTIES. The α-PbO nanocrystals were successfully decorated using sodium laureth sulfate (SLS) anionic surfactant. The method used is one-pot synthesis approach. The precursor used is lead nitrate (Pb(NO3)2). The UV-Vis spectrophotometer showed the absorption peak of α-PbO nanocrystals was seen at wavelength of 237 nm and an absorbance value of 0.7. The optical properties of PbO nanocrystals can be seen at the bandgap value of 4.2 eV. FT-IR spectroscopy showed the shift of absorption peak at the wavenumber of 1358 cm-1. XRD spectroscopy showed the crystals of PbO at diffraction angles (2θ) of 10-80o: 29.17, 32.54, 37.85, 39.62, 45.16, 46.21, 56.12, and 61.73 with miller indices of (111), (200), (201), (121), (220), (030), (311), and (032), respectively. The crystal size average of PbO was 56.32 nm. The results of PSA and PZC shows the particle size distribution of PbO is 71.5 nm with inter-particle charge of -25 mV. SEM-EDX data shows the PbO nanocrystals have an irregularly spherical with a compounds composition of Pb (83.12%) and O (16.88%). From the data of characterization, it can be concluded the PbO nanocrystals was successfully decorated using the surfactant anionic of sodium laureth sulfate.